2015
DOI: 10.1016/j.ajo.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Platelet Function and Disc Hemorrhage in Patients With Normal-Tension Glaucoma: A Prospective Cross-Sectional Study

Abstract: Our results suggest that platelet function is significantly associated with disc hemorrhage in patients with normal-tension glaucoma. Delayed absorption resulted from prolonged bleeding due to delayed platelet aggregation may have an effect on the detectability of disc hemorrhage in patients with normal-tension glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Meta-regression also failed to distinguish the exact source of the heterogeneity. Several factors, such as different characteristics of the populations, different quality of the included studies, different methods used to ascertain outcomes and exposure, different sample 44 Age, sex Chen (2005) 9 Age, SBP, DBP, glucose Motsko (2008) 54 Age, sex Lin (2010) 8 Age, gender, monthly income, and level of urbanization of the community in which the patient resided Lin (2010) 45 Age, sex Imai (2010) 42 Age, maximum temperature, increased abdominal circumference, elevated fasting glucose level, BP Ishikawa (2011) 52 Age, sex, DBP, IOP, and ocular perfusion pressure Newman-Casey (2011) 7 Age, sex, race, education level, household net worth, region of residence at the time of enrollment in the medical plan, cataract, pseudophakia or aphakia, macular degeneration, diabetic retinopathy, systemic hypotension, sleep apnea, and migraine headache Lee (2012) 46 Age, sex, SBP Lin (2012) 33 Age, sex, BMI, waist, SBP, DBP, fasting sugar, and postprandial sugar Kim (2014) 34 Age, sex, impaired glucose tolerance, hypertension, and baseline IOP Aptel (2014) 47 Age, sex, BMI, hypertension, and thyroid dysfunction Kim (2014) 43 Age, sex Chung (2014) 53 Age, sex Kim (2014) 55 Age, sex, myopia, fasting blood glucose Chen (2014) 48 Age, sex, hypertension, diabetes, CAD, and obstructive sleep apnea Sahinoglu-Keskek (2014) 41 Age Fujiwara (2015) 49 Age, sex, SBP, diabetes, cholesterol, HDLcholesterol, BMI, waist circumference, smoking habits, alcohol intake, and regular exercise Shim (2015) 32 Age, sex Chen (2016) 50 Age, sex Chen (2016) 51 Age, gender, and comorbidities of diabetes, hypertension, and CAD Ko (2016) 35 Age, gender, ethnicity, education, insurance, diabetes duration, BMI, hypertension, obstructive sleep apnea, and current smoker Kim (2016) 36 Age, sex, IOP, household income, exercise, education level, smoking status, alcohol consumption, and BMI Yokomichi (2016) 10 Age, sex, SBP, DBP, fasting plasma glucose Rim (2017) 37 Age, sex, hypertension, DM, chronic renal failure, atrial fibrillation, residence, income Lee (2017) 38 Age, sex, hypertension, DM, congestive heart failure, ischemic heart disease, atrial fibrillat...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-regression also failed to distinguish the exact source of the heterogeneity. Several factors, such as different characteristics of the populations, different quality of the included studies, different methods used to ascertain outcomes and exposure, different sample 44 Age, sex Chen (2005) 9 Age, SBP, DBP, glucose Motsko (2008) 54 Age, sex Lin (2010) 8 Age, gender, monthly income, and level of urbanization of the community in which the patient resided Lin (2010) 45 Age, sex Imai (2010) 42 Age, maximum temperature, increased abdominal circumference, elevated fasting glucose level, BP Ishikawa (2011) 52 Age, sex, DBP, IOP, and ocular perfusion pressure Newman-Casey (2011) 7 Age, sex, race, education level, household net worth, region of residence at the time of enrollment in the medical plan, cataract, pseudophakia or aphakia, macular degeneration, diabetic retinopathy, systemic hypotension, sleep apnea, and migraine headache Lee (2012) 46 Age, sex, SBP Lin (2012) 33 Age, sex, BMI, waist, SBP, DBP, fasting sugar, and postprandial sugar Kim (2014) 34 Age, sex, impaired glucose tolerance, hypertension, and baseline IOP Aptel (2014) 47 Age, sex, BMI, hypertension, and thyroid dysfunction Kim (2014) 43 Age, sex Chung (2014) 53 Age, sex Kim (2014) 55 Age, sex, myopia, fasting blood glucose Chen (2014) 48 Age, sex, hypertension, diabetes, CAD, and obstructive sleep apnea Sahinoglu-Keskek (2014) 41 Age Fujiwara (2015) 49 Age, sex, SBP, diabetes, cholesterol, HDLcholesterol, BMI, waist circumference, smoking habits, alcohol intake, and regular exercise Shim (2015) 32 Age, sex Chen (2016) 50 Age, sex Chen (2016) 51 Age, gender, and comorbidities of diabetes, hypertension, and CAD Ko (2016) 35 Age, gender, ethnicity, education, insurance, diabetes duration, BMI, hypertension, obstructive sleep apnea, and current smoker Kim (2016) 36 Age, sex, IOP, household income, exercise, education level, smoking status, alcohol consumption, and BMI Yokomichi (2016) 10 Age, sex, SBP, DBP, fasting plasma glucose Rim (2017) 37 Age, sex, hypertension, DM, chronic renal failure, atrial fibrillation, residence, income Lee (2017) 38 Age, sex, hypertension, DM, congestive heart failure, ischemic heart disease, atrial fibrillat...…”
Section: Discussionmentioning
confidence: 99%
“…One additional study was included after searching for references. 32 Ultimately, 28 studies, including 13 cross-sectional, 9,32-43 10 cohort or nested case-control, 7,10,44-51 and 5 case-control 8,52-55 studies were included in the present meta-analysis. Of these studies, 18 studies reported on the relationship between hyperlipidemia (hyperlipidemia or hypertriglyceridemia or hypercholesterolemia) and glaucoma, 7,8,32,34-39,44,45,47,48,50- 54 1 on blood highdensity lipoprotein-cholesterol (HDL-c) level and glaucoma, 55 1 on hyperlipidemia and OHT, 42 5 on blood triglyceride level and IOP, 9,10,33,43,46 2 on blood HDL-c level and IOP, 10,43 2 on total cholesterol level and IOP, 43,46 1 on low-density lipoprotein-cholesterol (LDL-C), 43 and 3 on hyperlipidemia and IOP.…”
Section: Literature Searchmentioning
confidence: 99%
“…24 In addition, platelet function has been shown to be associated with disc hemorrhage in patients with NTG because delayed platelet aggregation can cause prolonged bleeding, delaying absorption. 25 Thus, the occurrence of disc hemorrhage is a significant risk factor for glaucoma progression, whereas migraine, low OPP, and reduced platelet function are also related. In contrast, disc hemorrhage is also significantly associated with retinal blood vessel positional shift but not functional change, 26 suggesting that both vascular and mechanical factors are related to the presence of disc hemorrhage.…”
Section: Disc Hemorrhagementioning
confidence: 99%
“…Platelets indeed seem to play a role in this process. However, the primary risk factor for disc hemorrhages in these experiments was found to be delayed – instead of increased – platelet aggregation 22. A possible cause of platelet hyper-reactivity in patients with glaucoma may involve the pigment epithelium-derived factor (PEDF).…”
Section: Discussionmentioning
confidence: 85%
“…It has been postulated that microcirculatory defects, such as vasoconstriction and retention of blood, damage endothelial cells, leading to sub-endothelial collagen exposure which triggers platelet aggregation, subsequently causing ischemic injury of the optic nerve 12,16,20. The Ocular Hypertension Treatment Study demonstrated that occurrence of disc hemorrhage predisposes to the development of POAG,21 while later Shim et al22 claimed that micro-infarctions within the optic nerve head and retinal circulatory disorders may be the cause of disc hemorrhages in patients with normal-tension glaucoma 9,2224. Platelets indeed seem to play a role in this process.…”
Section: Discussionmentioning
confidence: 99%